Guillain-Barré Syndrome Masquerading As Cervical Myelopathy - Mallick, Uzzwal Kumar; Alam, Badrul; Asaduzzaman, Mohammad (Bangladesh Critical Care Journal, 2017)
Guillain-Barré syndrome (GBS) is an acute inflammatory demyelinating polyneuropathy. In typical cases, the first symptoms of GBS are pain, numbness, paresthesia, weakness in the limbs. Autonomic involvement is common and causes urinary retention and ileus. Most of these symptoms overlap with those of cervical myelopathy. Therefore, correct diagnosis of GBS in a patient with symptomatic cervical myelopathy or in a patient with atypical manifestations of GBS can be difficult, especially early in the course of GBS. We report a 60-year-old man who was admitted to the neurosurgery department with worsening neck pain, numbness and weakness in the hands initially thought to be secondary to progressive cervical myelopathy. However, his symptoms rapidly progressed to flaccid areflexic quadriparesis and respiratory difficulty within few days and shifted to ICU for ventilator support. Electrophysiological studies and cerebrospinal fluid analysis were consistent with an acquired demyelinating polyradiculoneuropathy. We planned for immunotherapy with intravenous immunoglobulin , but his condition was improving day by day with conservative treatment , so immunotherapy with intravenous immunoglobulin was not initiated. Any patient presenting as unexplain Cervical myelopathy, GBS should be kept in mind before planning any surgical intervention. Bangladesh Crit Care J September 2017; 5(2): 129-131